2014
DOI: 10.1002/pro.2427
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori RNA polymerase α‐subunit C‐terminal domain shows features unique to ɛ‐proteobacteria and binds NikR/DNA complexes

Abstract: Bacterial RNA polymerase is a large, multi-subunit enzyme responsible for transcription of genomic information. The C-terminal domain of the a subunit of RNA polymerase (aCTD) functions as a DNA and protein recognition element localizing the polymerase on certain promoter sequences and is essential in all bacteria. Although aCTD is part of RNA polymerase, it is thought to have once been a separate transcription factor, and its primary role is the recruitment of RNA polymerase to various promoters. Despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In fact, the evidence that the unique NikR binding site upstream of the urease promoter is clearly associated with nickel-responsive repression of the divergent Nrr2 transcript, poses the question whether NikR binding to this operator also directly activates the ure promoter. A recent study suggested that NikR has acquired a RNA polymerase (RNAP) interacting domain50 and could therefore act as transcriptional activator. In this scenario, it is surprising to notice that upon the acquisition of a RNAP interacting domain a key transcription factor like NikR is engaged in the control of only one (urease) operon.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the evidence that the unique NikR binding site upstream of the urease promoter is clearly associated with nickel-responsive repression of the divergent Nrr2 transcript, poses the question whether NikR binding to this operator also directly activates the ure promoter. A recent study suggested that NikR has acquired a RNA polymerase (RNAP) interacting domain50 and could therefore act as transcriptional activator. In this scenario, it is surprising to notice that upon the acquisition of a RNAP interacting domain a key transcription factor like NikR is engaged in the control of only one (urease) operon.…”
Section: Discussionmentioning
confidence: 99%
“…RNA polymerase is an indispensible protein responsible for transcription of DNA into RNA. Bacterial RNA polymerase consists of α, β and ω subunits (α2ββ'ω) [1]. β and β' are the largest subunits of bacterial RNA polymerase possessing catalytic site, and β and β' subunits in H. pylori exist as a single fused protein [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial RNA polymerase consists of α, β and ω subunits (α2ββ'ω) [1]. β and β' are the largest subunits of bacterial RNA polymerase possessing catalytic site, and β and β' subunits in H. pylori exist as a single fused protein [1,5]. α subunit binds to β and β' subunits and stabilizes the complex, and ω subunit has both structural and functional role [1,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations